Decision Support System For Prospective Recipients Of The Healthy Indonesia Card (Kis) In The Village Of Bah Sidua Dua With The Analytical Hierarchy Process (AHP) Method: Decision Support System For Prospective Recipients Of The Healthy Indonesia Card (Kis) In The Village Of Bah Sidua Dua With The Analytical Hierarchy Process (AHP) Method - Elpridawati Purba; Hengki Tamando Sihotang (Institute of Computer Science (IOCS), 2019)
This study discusses how to discuss a support system that is used to assist the village government in negotiations for potential beneficiaries in the village of Bah Sidua dua as serdang bedagai regencies. The method used in this research is Analyticah Hierarchy Process (AHP), because this method is widely used in solving problems involving multi criteria. SPK is a system that can help someone to make decisions of various types that are done accurately and in accordance with the desired goals.